Estrategias motivacionales, su incidencia en el desarrollo del proceso enseñanza-aprendizaje de lengua y literatura en estudiantes de básica elemental, unidad educativa renán olmedo gonzález, cantón el empalme - Alcívar Quijije, María Gisella (2015)
The research presented below and also put at your disposal represents the continuous work performed in this year Renan Olmedo Education Unit for the future of children who are educated there, but now complexed them a problem broad and complex approach such as the poor school performance. The research emphasis falls on the subject of language and literature, which is taken up with the math as raw materials in the process of a student's academic training. In the same way you can highlight that quantitative no experimental mode for the process of collection and information gathering was chosen. This theme is based that through education the new society is forged so states Kant "education is an art whose main aim is the pursuit of human perfection" in this way if there are difficulties in a specific area of the formation of a individual, society and the people involved are obliged to seek immediate solutions, in this case the works was raised in Olmedo Renan Education Unit The main objective of this research is to demonstrate the influence of the use of motivational strategies in the teaching - learning of children in the seventh xiii year of basic education by identifying the school performance as a channel for measuring the results achieved by the students (Requena, 1998). Meanwhile you must know that in this process - learning the active participation of three entities as essential as: school, students and parents. Thus, in this study the knowledge of the three areas covered, as the survey presented show data for the three mentioned areas and the work that they performed, that were related in the investigation, being able to know the following: In the area of motivation 78% of students they need help to reinforce the content learned, but unfortunately did not receive guidance and / or some motivation. Likewise with respect to school performance generally it reaches 81% or minimum grade average, and the lack of habits and study techniques as lack of time (63%) and reading (84%). Linking these two variables can be obtained if there is a direct relationship, it also raises the discretion to change the methodology of classes because for 43% of classes students are unpleasant and boring due to the methodology used. To conclude this investigation is a pioneer in the educational establishment especially in the area of language arts, will represent an incentive for future generations who are interested in this area of work